ANALISIS STRATEGI PENGEMBANGAN PELABUHAN KENDARI - Takdir, Riyan Abdillah; Buana, I Gusti Ngurah Sumanta (Badan Pengkajian dan Penerapan Teknologi, 2019)
The increase in cargo flows that are not supported by adequate port facilities has hampered the Nusantara Kendari Port logistics process. The port development strategy by relocating Nusantara port functions to Bungkutoko Port is considered a solution to the limitations of the Nusantara Port. The purpose of this study was to analyze the impact of the planned transfer of the port by observing several performance indicators. The port performance indicators used were yard occupancy ratio (YOR), berth occupancy ratio (BOR) and shed occupancy ratio (SOR). The results showed that the Nusantara Port performance indicator values before the relocation were 118.57% for YOR of container, 24.3% for YOR of general cargo, 62.55% for SOR of general cargo, 17.71% for BOR of passengers and 76.91% for BOR of container and general cargo. Whereas after the relocation there were several performance indicator values that did not reach operational performance standards. Those values were 75.37% for BOR of container in 2028, 70.96% for YOR of container in 2033 and 67.21% for SOR of general cargo in 2021. Based on the results, it was concluded that an alternative development strategy was necessary to optimize the value of Kendari Port performance indicators.